Associations and young people during the Tunisian transition: pluralism, socialisation, and democratic legitimation?. Issue 2 (4th March 2021) - Desrues, Thierry; Velasco Arranz, Ana
ABSTRACT: In Tunisia, during the initial years of the democratic transition, the number of registered associations has doubled. The few studies available point out that a significant proportion of the new associations' membership is made up of young people. This specific participation of young people in the network of associations that emerged from 2011 onwards is not very well-known either. In this article, we wish to contribute primarily to providing information that facilitates understanding of the changes that have taken place in the associative sector and in the participation of young people in it. Furthermore, we believe that Tunisia is, in a way, a 'laboratory' in which civic participation in contexts of democratic consolidation can be explored. Specifically, using data obtained from two surveys conducted in 2015 and 2016 we propose, first, to examine the profile of the young people active in the associations and the areas in which their associations intervene, in order to see to what extent the argument regarding the plural representation of the heterogeneity of young people can be verified through the network of associations. Second, we aim to evaluate the contribution of socialisation through associations to the inculcation of a democratic culture that would be verified in the electoral behaviour of young association activists. Third, we aim to open a debate about the possible 'macro' or systemic effects of these data; that is to say, about the representation of pluralism and diversity in Tunisian society, as well as the legitimation of democratic institutions.